1994
DOI: 10.1002/pc.750150303
|View full text |Cite
|
Sign up to set email alerts
|

The fracture behavior of rubber‐toughened, short‐fiber composites of nylon 6,6

Abstract: This study critiques the use of both rubber particles and short-glass fibers for the improvement of polymer fracture toughness ( K ). Although dry neat nylon is brittle with only a moderate K , value (4.2 M P a g ) , additions of either second phase produce rising K,-curves and associated high K , values (8.1 M P a 6 for rubber-toughened nylon, and 10.0 M P a G for 17 vol% glass-fiber neat nylon). In the rubber-modified resin, the high K, value is associated with extensive plastic blunting at the crack tip. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…It is definite that the enhancement in the flexural strength is attributed to the reinforcement of glass fiber with a high aspect ratio. Percorini and Herzberg 25 and Mohd Ishak et al 4 reported similar results on rubber-toughened short glass fiber nylon 6.6 composites and short glass fiber-reinforced CSR-PBT, respectively. The inclusion of 10 wt % of either AX8900 or EXL2314 into the SGF-reinforced PBT adversely affected the flexural properties.…”
Section: Fracture Testsupporting
confidence: 77%
“…It is definite that the enhancement in the flexural strength is attributed to the reinforcement of glass fiber with a high aspect ratio. Percorini and Herzberg 25 and Mohd Ishak et al 4 reported similar results on rubber-toughened short glass fiber nylon 6.6 composites and short glass fiber-reinforced CSR-PBT, respectively. The inclusion of 10 wt % of either AX8900 or EXL2314 into the SGF-reinforced PBT adversely affected the flexural properties.…”
Section: Fracture Testsupporting
confidence: 77%
“…15,16 The incorporation of about 20 vol % of finely dispersed ethylene propylene diene monomer rubber particles into nylon 6,6 reduced the tensile strength of the nylon 6,6 matrix from 80 to about 50 MPa. 17 As for the tensile strain, the trend shown in Figure 4 is rather unexpected. The addition of CSR modifiers did not improve the tensile strain of the PBT.…”
Section: Kinetics Of Moisture Absorptionmentioning
confidence: 85%
“…Consequently, blending of both glass fi bres and rubber with thermoplastics seems to be a logical way to optimize important properties of thermoplastics. Surprisingly, though, the number of such studies conducted, mainly in the last decade, is small (see, for example, Kinloch et al, 1985;Kelnar, 1991;Nair and Shiao, 1992;Pecorini and Hertzberg, 1994;Shiao et al, 1994;Wong et al, 1995;Azari and Boss, 1996;Din and Hashemi, 1997;Nair et al, 1997a;Nair et al, 1997bNair et al, , 1998Laura et al, 2000;Cho and Paul, 2001;Sui et al, 2001). Among these studies, nylon 66 has received less attention in terms of selecting the appropriate impact modifi ers for it (Pecorini and Hertzberg, 1994;Wong et al, 1995;Nair et al, 1997a;Nair et al, 1997bNair et al, , 1998Sui et al, 2001).…”
Section: Sample Preparationmentioning
confidence: 99%